Journal of Intelligent & Robotic Systems with a special section on Unmanned Systems - Valavanis, Kimon P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The Journal of Intelligent and Robotic Systems (JINT) publishes original, peer-reviewed, invited, survey and review papers. These papers promote and disseminate scientific knowledge and information in the fields of system of systems, generalized system theory, distributed intelligent systems, bioengineering, robotics and automation, human-robot interaction, human-machine interfaces and interaction, robot ethics, social and service robotics, medical robotics, mechatronics, unmanned systems, multi-robot teams and networked swarms, machine intelligence, learning, system autonomy and autonomous systems, design for autonomy, cyber physical systems, and other related areas in which cutting edge technologies have been developed and applied to model, design, build and test complex engineering and autonomous systems. Every JINT issue includes a dedicated section devoted to Unmanned Systems with the aim to be at the forefront of reporting scientific breakthroughs in this highly expanding and challenging area. JINT offers a unique forum and advantage, second to none, because it encourages original contributions referring and related to: unmanned aviation airworthiness; unmanned aviation policies, procedures, and regulations; certification issues; operational constraints; UAS safety, security, and risk analysis assessment; UAS reliability; operational frequency management; legal, ethical and privacy issues, and technology standardization. JINT lays the foundation for a common framework for publication of ideas, derivation and testing of techniques that combine theory, science, engineering, and mathematics, leading to future innovations and novel technologies. The journal aims at bridging the gap between theory and practice, and intends to stimulate interaction between faculty, researchers, engineers and practitioners from academia, industry and government focusing on theoretical and applied research in all areas of intelligent systems and robotics. .
Keywords: Control engineering; Robotics; Automation; Electrical engineering; Artificial intelligence; Mechanical engineering; Control, Robotics, Automation; Electrical and Electronic Engineering; Artificial Intelligence; Mechanical Engineering